RELASI TUHAN- MANUSIA : PENDEKATAN ANTROPOLOGI METAFISIK TERHADAP Gurindam Duabelas Karya Raja Ali Haji - Irwandra Irwandra (An-Nida', 2013)
penetrated into thematic domains it urgens sustain life and enhance mutual existing chapters.